2006
DOI: 10.1128/iai.02035-05
|View full text |Cite
|
Sign up to set email alerts
|

Borrelia burgdorferi Lacking BBK32, a Fibronectin-Binding Protein, Retains Full Pathogenicity

Abstract: BBK32, a fibronectin-binding protein of Borrelia burgdorferi, is one of many surface lipoproteins that are differentially expressed by the Lyme disease spirochete at various stages of its life cycle. The level of BBK32 expression in B. burgdorferi is highest during infection of the mammalian host and lowest in flat ticks. This temporal expression profile, along with its fibronectin-binding activity, strongly suggests that BBK32 may play an important role in Lyme pathogenesis in the host. To test this hypothesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
92
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(99 citation statements)
references
References 62 publications
7
92
0
Order By: Relevance
“…Previous studies have identified several important virulence determinants, such as OspA, OspC, DbpB, DbpA, and BBK32 (19,31,39,54,60,67). For instance, B. burgdorferi strictly requires OspC to establish an infection in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified several important virulence determinants, such as OspA, OspC, DbpB, DbpA, and BBK32 (19,31,39,54,60,67). For instance, B. burgdorferi strictly requires OspC to establish an infection in mice.…”
Section: Discussionmentioning
confidence: 99%
“…This may therefore translate into a lack of attenuation of infectivity following short-or long-term infection. Inactivation of proteins in B. burgdorferi that serve as adhesins, such as BBK32 (38,61) and Bgp (49), has resulted in either partial or no attenuation of infectivity, suggesting the role of multiple borrelial determinants in initiation and maintenance of infection. Hence, it is interesting to speculate that infectivity analysis of a BBA64/ BBA65/BBA66-negative triple mt will help further characterize the role of a subset of pgf 54 family members in the colonization and dissemination of B. burgdorferi within the mammalian host.…”
mentioning
confidence: 99%
“…The current results demonstrate that not all genes whose expression is coordinately regulated with those required for virulence are themselves necessary for that process. It should be noted that there are numerous contradictory reports about the roles of other RpoS-dependent genes (e.g., dbpA, bbk32, and bba64) in mammalian infection, although these discrepancies may depend on the experimental mode of infection (3,20,31,34,35,(42)(43)(44)(45). Our findings underscore the necessity to demonstrate required protein function by mutagenesis experiments, rather than reliance on correlative data alone.…”
Section: Discussionmentioning
confidence: 69%